Morning, noon & night. - Sheldon, Sidney; Douglas, Kirk, 1916- (Beverly Hills, CA : Dove Audio, 1995)
When a wealthy tycoon drowns off the coast of Corsica, a woman claiming to be his daughter appears at the funeral, looking to claim a share of his estate. As the family seeks to learn whether she is genuine or an imposter, a web of blackmail, drugs, and murder emerge from behind the facade of fame and glamour.
Abridged.
In container (18 cm.).
Performed by Kirk Douglas.
Keywords: Inheritance and succession -- Fiction; Detective and mystery stories; Domestic fiction